A comprehensive role evaluation and mechanism exploration of POGLUT2 in pan-cancer - Xu, Xianyun; Xie, Guangming; Xie, Mingfeng; Liu, Qian (Frontiers in Oncology, 2022)
Objective: To evaluate the role of POGLUT2 in pan-cancer through bioinformatic analysis and experimental verification. Methods: Expression, gene mutation and amplification, methylation and CNA of POGLUT2 was evaluated using the TCGA, CCLE and GTEx database. Moreover, POGLUT2 on survival and disease progression in pan cancer was performed using the TCGA data. Immune infiltration and tumor microenvironment evaluation was assessed by ImmuneScore, ImmuCellAI and TIMER database. POGLUT2 correlated drug resistance analysis was performed using GDSC2 database. Furthermore, POGLUT2 knockdown breast cancer cells was established, followed by in vitro biological function assays and in vivo tumor growth study. The mechanisms of POGLUT2 in breast cancer was briefly evaluated via its connection with notch signaling. Results: Increased levels of POGLUT2 was found in multiple types of cancer tissues and cell lines. Moreover, increased gene mutation and amplification, methylation and CNA of POGLUT2 was found in several types of cancers. POGLUT2 was mainly expressed in stromal cells as verified by StromalScore, ESTIMATEScore, ImmuneScore and Tumor purity and POGLUT2 was positively correlated with cancer associated fibroblasts, macrophages, monocytes and neutrophils in the tumor microenvironment. In vitro and in vivo results showed that POGLUT2 knockdown could delay the tumor growth and progression. Notch signaling components were related with the function of POGLUT2. Conclusions: Increased levels of POGLUT2 could result in the dysregulated immune cell infiltration and tumor microenvironment, thereby affecting the tumor development and progression through Notch related signaling.